Formation of practical competences of future physical therapists and occupational therapists in the process of professional training. - Logush, Lesya; Oliinyk, Mariya (International Journal of Educational Theory and Practice, 2021)
bstractThe article is devoted to the study of the formation of practical competencies of future physical therapists and occupational therapists in the process of professional training. The aim of the research was to study the impact of certain methods on the quality of future physical therapists and occupational therapists’skills and abilities during clinical neurological practice. The research methods such as observation, questionnaire, success analysis and mathematical processing of the obtained data were applied in the work.As a result of an experiment conducted at the clinical bases of neurological practice in Chernivtsi with the fourth year students, it was discovered that the proposed pedagogical techniques (usage of methodical guidelines, patterns and neurological and physiotherapeutic examinations schemes, development of individual rehabilitation programs) and practice defencesconduction with practical skills demonstration increase the efficiency of theoretical knowledge acquisition and improve the future specialists skills in physical therapy and occupational therapy.Clinical practice helps to improve the training of physical therapists and occupational therapists for future professional activities.The combination of clear methodological recommendations with independent research work, substantiation of physiotherapeutic interventions and practice of practical skills allows students to bring their preparation as close as possible to the requirements for the Standard of Higher Education in Ukraine
Keywords: фізична терапія; студент; competencies formation;future specialists;professional training;clinical practice;individual rehabilitation program;practical skills.